Representations of internationalisation at a Portuguese Higher Education Institution: From institutional discourse to stakeholders’ voices (Revista Lusófona de Educação, 2020)
Internationalisation has become a major concern of higher education institutions around the world, featuring as a goal in their mission statements and agendas. Yet, the ways it is perceived and addressed vary greatly. In some cases, internationalization is viewed as a service to export, whilst in other cases, the focus falls on the acquisition and development of graduates’ global and intercultural competences. This paper reports on a study that aimed to understand how internationalization is perceived at a Portuguese Higher Education Institution. To achieve this goal institutional policy documents were collected, and semi-structured interviews were conducted with members of governing and coordinating bodies, as well as with academic and non-academic staff. Results from the thematic analysis suggest that internationalization is seen as a priority at the highest strategic level, being associated with a set of activities (student mobility, international research projects, and English-medium instruction) and with a set of desired outcomes (increased revenues and institutional visibility). Moreover, stakeholders consider internationalisation a valuable asset for the development of students’ skills, expressing positive attitudes towards such initiatives as “internationalisation at home”. Based on these findings, recommendations for a more comprehensive and sustainable internationalisation approach applicable to other contexts are put forward.Keywords: internationalisation; Portuguese higher education; social representations